MEDICATION ADMINISTRATION TIME STUDY (MATS): HEALTH PROFESSIONALS PERFORMANCE OF MEDICATION ADMINISTRATION - Waleed Ashawy Alshammari 1, Salah Asmair Alharbi 2, Amer Maseer Aldhafeeri 3, Mohammad Owaid Aldhafeeri 4, Sultan Abdullah Alharbi 5, Waleed Owaid Aldhafeeri 6, (Chelonian Research Foundation, 2022)
Medication administration is a critical component of patient care that requires precision, attention to detail, and adherence to established protocols. Errors in medication administration can lead to adverse patient outcomes, increased healthcare costs, and legal liabilities. This study aims to investigate the performance of health professionals in medication administration and identify factors that influence the time taken to complete the process. The Medication Administration Time Study (MATS) employed a cross-sectional observational design to collect data from a sample of health professionals across various healthcare settings. Participants were observed during medication administration rounds, and data on time taken, interruptions, distractions, and adherence to protocols were recorded. The findings revealed significant variations in medication administration times among health professionals, with factors such as experience, workload, and work environment contributing to the observed differences. The study highlights the need for targeted interventions to improve medication administration efficiency and reduce the risk of errors. Recommendations include the implementation of standardized protocols, enhanced training programs, and the use of technology to support medication administration processes. The insights gained from this study can inform policy and practice changes to enhance patient safety and optimize healthcare delivery. Keywords: medication administration, health professionals, time study, patient safety, healthcare quality